Mordenite and preparation method thereof
The conversion of mordenite into a hollow structure through pretreatment and reaction steps has solved the problem that the existing technology cannot synthesize hollow mordenite, realized the preparation of mordenite with hollow structure, and expanded its application potential in drug carriers and catalytic materials.
Patent Information
- Application Number
- CN202310867532.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-07-15
AI Technical Summary
The prior art cannot effectively synthesize mordenite with hollow structures and lacks industrial production methods.
The mordenite is contacted with an ammonia-containing gas by pretreatment steps, and then reacted with an aluminum-containing compound, an alkali source, a silicon-containing compound and ethylenediaminetetraacetic acid, and treated under calcination conditions to form a hollow mordenite.
The successful preparation of mordenite with hollow structure solved the problem that existing methods cannot synthesize hollow mordenites, and provided new application prospects such as drug carriers and catalytic materials.
Smart Images

Figure CN119320145A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic zeolite material synthesis, and relates to a mordenite and a preparation method thereof, in particular to a hollow mordenite and a preparation method thereof. Background Art
[0002] Mordenite was first synthesized by Barrer in the 1940s. Due to its high silicon-aluminum ratio, mordenite has excellent heat and acid resistance. It is widely used in industry as an adsorbent for separation of gas or liquid mixtures and a catalyst for petrochemical and fine chemicals. It is mainly used in catalytic cracking, hydrocracking, hydroisomerization of paraffins and other oil refining processes.
[0003] CN106517239A discloses a pillared layered mordenite and a preparation method thereof. The invention uses silica sol as a silicon source, sodium aluminate as an aluminum source, and hexamethyleneimine as a template agent. A dynamic hydrothermal synthesis method is firstly adopted to synthesize a swellable layered mordenite. Then, the obtained swellable layered mordenite is swollen with hexadecyl polyoxyethylene hexadecyl ammonium bromide. Finally, the swollen layered mordenite is reacted with ethyl orthosilicate to pillar the zeolite.
[0004] CN102190316A discloses a method for synthesizing mesoporous mordenite, which comprises mixing a silicon source, an aluminum source, an organic amine structure directing agent SDA, a polymer mesoporous template agent R and water, wherein the silicon source, the aluminum source, the organic amine structure directing agent SDA and water are mixed in the mixture, and the mixture is crystallized at 100 to 200° C. for 1 to 10 days to obtain a crystalline product, and the crystalline product is washed, dried and calcined to obtain the mesoporous mordenite. The polymer mesoporous template agent is selected from starch, dextrin, cellulose, polyethylene glycol, polyvinyl alcohol, polyether, polyvinyl formal or polyvinyl butyral.
[0005] CN115536040A discloses a nano lotus leaf-shaped aluminum-rich mordenite molecular sieve and a synthesis method and application thereof. The preparation steps are as follows: an aluminum source is added to a NaOH solution and mixed to obtain a solution A; a template agent, a silicon source, an aluminum-rich agent, and a crystal growth inhibitor are then added to the solution A in sequence and stirred to form a uniform sol B; finally, the sol B is stirred to a dry gel state, water is added, and then the sol is transferred to a reactor to form a uniform and stable gel under high-temperature vibration conditions; after washing, filtering, drying, roasting, ammonia exchange, and roasting, a nano lotus leaf-shaped aluminum-rich MOR molecular sieve with a sheet thickness of 10 to 100 nm is obtained.
[0006] At present, hollow or hollow zeolite molecular sieve materials are a special type of functional materials. The research on related materials has become a hot topic in the field of chemistry and new materials. Hollow zeolite molecular sieves have unique physical and chemical properties such as multi-level structure and large specific surface area, showing broad application prospects in shape-selective adsorbents, catalysts, drug sustained-release agents and microreactors, and have received more and more attention.
[0007] At present, there is no industrial production method of hollow-structured mordenite in the published reports of the prior art, so it is of great significance to develop a synthesis method of hollow-structured mordenite. Summary of the invention
[0008] The present invention provides a mordenite and a preparation method thereof, and provides a mordenite with a hollow structure which is completely different from the existing mordenite structure. The preparation method has a simple synthesis process, and solves the technical problem that the hollow mordenite cannot be synthesized by the existing method for synthesizing hollow zeolites.
[0009] Based on the above, the technical solution of the present invention mainly includes the following aspects:
[0010] The first aspect of the present invention provides a mordenite zeolite having a mordenite structure and characterized by a transmission electron microscope as a single crystal particle with a hollow structure, wherein the center of the crystal is in a hollow state.
[0011] Preferably, in the above-mentioned mordenite, the particle diameter of the mordenite crystal is 90 to 1000 nm, preferably 100 to 900 nm.
[0012] Preferably, in the above-mentioned mordenite, the shell thickness of the mordenite crystal particles is 25 to 360 nm, preferably 30 to 300 nm.
[0013] Preferably, in the above-mentioned mordenite, the specific surface area of the mordenite is 270 to 590 m 2 / g, preferably 300 to 560 m 2 / g.
[0014] Preferably, in the above-mentioned mordenite, the pore volume of the mordenite is 0.1 to 0.3 cm 3 / g.
[0015] Preferably, in the above-mentioned mordenite, the acid content of the mordenite is 0.05 to 0.24 mmol / g.
[0016] Preferably, in the above-mentioned mordenite, the silicon-aluminum ratio of the mordenite is 9 to 50, preferably 10 to 45, calculated as oxide.
[0017] The second aspect of the present invention provides a method for preparing mordenite, the preparation method comprising the following steps:
[0018] (1) under pretreatment conditions, the mordenite is contacted with an ammonia-containing gas for pretreatment, and after the treatment, the mordenite is washed, separated and dried to obtain the pretreated mordenite;
[0019] (2) under reaction conditions, pretreated mordenite, an aluminum-containing compound, an alkali source, a silicon-containing compound, ethylenediaminetetraacetic acid, and water are uniformly mixed and reacted, and the product obtained by the reaction is washed with water, separated, and dried to obtain a zeolite precursor;
[0020] (3) After treating the zeolite precursor under calcination conditions, hollow mordenite is obtained.
[0021] The third aspect of the present invention provides a method for preparing mordenite, the preparation method comprising the following steps:
[0022] Step (1): synthesizing a zeolite precursor, the synthesis steps comprising:
[0023] (1) under pretreatment conditions, the mordenite is contacted with an ammonia-containing gas for pretreatment, and after the treatment, the mordenite is washed, separated and dried to obtain the pretreated mordenite;
[0024] (2) under reaction conditions, pretreated mordenite, an aluminum-containing compound, an alkali source, a silicon-containing compound, ethylenediaminetetraacetic acid, and water are uniformly mixed and reacted, and the product obtained by the reaction is washed with water, separated, and dried to obtain a zeolite precursor;
[0025] Step (ii): Under ammonium exchange conditions, the obtained zeolite precursor is subjected to ammonium exchange treatment, and then washed, separated, dried and calcined to obtain hydrogen-type hollow mordenite.
[0026] Preferably, in the above-mentioned preparation method of mordenite, the mordenite in step (1) is a MTW structure zeolite, which can be selected from commercial products in the field, or obtained by an existing synthesis method. More specifically, the properties of Y zeolite are generally as follows: the particle diameter of the crystal is 90 to 1000 nm; the specific surface area is 300 to 600 m 2 / g, pore volume is 0.09~0.31cm 3 / g.
[0027] Preferably, in the above-mentioned preparation method of mordenite, the pretreatment in step (1) is a gas-solid two-phase reaction between mordenite and ammonia-containing gas, and the mordenite is contacted with the ammonia-containing gas for pretreatment. The specific reaction process is as follows: a support is provided in the reactor, the mordenite is placed on the support, and ammonia water and water are added to the lower part of the reactor support; there is no direct contact between the mordenite and the ammonia water, and further, the mass ratio of ammonia water, mordenite and water is 12-28:8-25:100, preferably 15-25:10-20:100; the ammonia water is industrial ammonia water, an aqueous solution containing 25% to 28% ammonia.
[0028] Preferably, in the above-mentioned method for preparing mordenite, the pretreatment conditions in step (1) are as follows: the pretreatment temperature is 400-900° C., preferably 450-850° C., and the pretreatment time is 0.5-6 hours, preferably 1-5 hours.
[0029] Preferably, in the above-mentioned preparation method of mordenite, the washing, separation and drying in step (1) can be selected from various existing operation modes in the art. Preferably, in the present application scheme, the washing is generally washing with deionized water until the filtrate is neutral, and the washing can be performed several times, usually multiple times, such as 1-10 times. Separation is to separate the liquid and solid phases after washing, and any of the methods that can achieve liquid-solid phase separation, such as filtration and centrifugal separation, can be used. The drying is generally drying at 100-140°C for 5-15h.
[0030] Preferably, in the above-mentioned method for preparing mordenite, the alkali source in step (2) is an inorganic alkali, specifically one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.
[0031] Preferably, in the above-mentioned preparation method of mordenite, the aluminum-containing compound in step (2) is an aluminum-containing inorganic salt, and the acid ion of the aluminum-containing inorganic salt can be one or more of sulfate, aluminate, nitrate, and chloride. Specifically, the aluminum-containing compound is selected from one or more of sodium aluminate, aluminum sulfate, aluminum chloride, and aluminum nitrate.
[0032] Preferably, in the above-mentioned method for preparing mordenite, the silicon-containing compound in step (2) is one or more of white carbon black, silica gel and silica sol.
[0033] Preferably, in the above-mentioned method for preparing mordenite, the mass ratio of the alkali source, the aluminum-containing compound, the silicon-containing compound, the pretreated mordenite, the ethylenediaminetetraacetic acid, and the water in step (2) is 0.8-2.5:0.8-2.1:2.5-6:8-25:0.8-3:100, preferably 1-2:1-2:2-4:10-20:1-2.5:100.
[0034] Preferably, in the above-mentioned method for preparing mordenite, the reaction conditions of step (2) are: reaction temperature 70-150° C., preferably 80-120° C., and reaction time 19-32 h, preferably 20-30 h.
[0035] Preferably, in the above-mentioned method for preparing mordenite, the drying conditions in step (2) are: drying temperature is 80-150° C., and drying time is 1-20 h.
[0036] Preferably, in the above-mentioned method for preparing mordenite, the ammonium treatment in step (ii) can adopt any of the existing ammonium exchange methods in the art; the ammonium exchange treatment is performed at least once, preferably 3 to 5 times.
[0037] Preferably, in the above-mentioned preparation method of mordenite, the ammonium exchange treatment in step (ii) is to mix the zeolite precursor, ammonium salt and water obtained after drying in step (2) for ion exchange treatment, and the mass ratio of the zeolite precursor, ammonium salt and water obtained after drying in step (2) is 8-25:8-25:100, preferably 10-20:10-20:100, based on the mass ratio. The ammonium salt can be one or more of ammonium nitrate, ammonium chloride and ammonium sulfate, preferably ammonium nitrate.
[0038] Preferably, in the above-mentioned method for preparing mordenite, the ammonium exchange conditions in step (ii) are: the ion exchange temperature is 70-100° C., preferably 80-90° C., and the ion exchange time is 1-5 h, preferably 2-4 h.
[0039] Preferably, in the above-mentioned preparation method of mordenite, the washing and separation in step (ii) can be selected from various existing operation modes in the art. Preferably, in the present application scheme, the washing is generally washing with deionized water until the filtrate is neutral, and the washing can be performed several times, usually multiple times, such as 1-10 times. Separation is to separate the liquid and solid phases after washing, and any of the methods that can achieve liquid-solid phase separation, such as filtration and centrifugal separation, can be used.
[0040] Preferably, in the above-mentioned method for preparing mordenite, the drying conditions in step (ii) are as follows: the drying temperature is 80-150° C., and the drying time is 1-20 hours.
[0041] Preferably, in the above-mentioned preparation method of mordenite, the calcination in step (ii) is carried out in the presence of an oxygen-containing gas, the volume fraction of oxygen in the oxygen-containing gas is 10 to 100%, specifically, it can be air, oxygen, a mixture of oxygen and an inert atmosphere, the inert atmosphere is nitrogen and / or an inert gas; the calcination conditions are as follows: the calcination temperature is 400 to 600°C, and the high-temperature calcination treatment is 1 to 10 hours.
[0042] The third aspect of the present invention provides a mordenite obtained by the above preparation method. The mordenite has a hollow structure and can be used as a carrier of molecules such as drugs, and can also be used as an adsorbent or a catalytic material.
[0043] Based on the above content, the technical effects of the mordenite and the preparation method thereof in the technical solution of the present invention are analyzed as follows:
[0044] In the present technical scheme, the mordenite is first pretreated. During the pretreatment process, under the action of ammonia-containing gas, the silicon and aluminum elements in the mordenite structure are rearranged. During the rearrangement process, the aluminum element may migrate to the outside of the zeolite crystal, forming a gradient distribution of the aluminum element inside and outside the mordenite crystal. Analysis shows that this gradient distribution may promote the formation of a hollow structure, and under the action of ammonia, the crystal still maintains a relatively complete structure.
[0045] In the present technical scheme, the reaction in step (2) is different from the existing hydrothermal synthesis reaction. During the reaction, inorganic bases, silicon-containing compounds, aluminum-containing compounds, ethylenediaminetetraacetic acid react with mordenite, and the aluminum element enters the outside of the mordenite crystal, while the inside of the mordenite crystal undergoes a dissolution reaction, thereby forming a hollow form. In this process, the silicon-containing compound basically does not enter the zeolite crystal skeleton. After analysis, it is believed that it only plays a role in stabilizing the system. However, in the absence of silicon-containing compounds, mordenite cannot be effectively transformed into a hollow structure. Ethylenediaminetetraacetic acid can stabilize the crystal structure and prevent the crystal structure from collapsing. Moreover, the ratio of each material in the raw material system in this scheme is not within the effective ratio range of the existing mordenite synthesis.
[0046] Combined with the above analysis, this technical solution provides a new hollow structure mordenite and its preparation method, which solves the problem that the existing method for synthesizing hollow structure zeolite cannot directly synthesize hollow mordenite. The existing public method for synthesizing hollow zeolite is not applicable to the preparation of hollow mordenite, because different types of zeolites have different crystal structures, and thus exhibit different physical and chemical properties. Just as it is well known that the synthesis methods of different types of zeolites are not completely universal, the preparation of hollow structure zeolites cannot be directly transferred between zeolites of different properties, and different types of hollow zeolites cannot be obtained by directly replacing the types of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a transmission electron microscope photograph of the mordenite sample obtained in Example 1.
[0048] Figure 2 This is a transmission electron microscope photograph of the mordenite sample obtained in Comparative Example 1.
[0049] Figure 3 This is the XRD spectrum of the mordenite sample obtained in Example 1.
[0050] Figure 4 The XRD spectrum of the mordenite sample obtained in Comparative Example 1. DETAILED DESCRIPTION
[0051] The technical solutions and effects of the present invention are further described below in conjunction with embodiments, but are not limited to the following embodiments.
[0052] In this paper, the pore structure of zeolite materials was characterized by N2 adsorption-desorption and tested by a physical adsorption instrument from Micromeritics, USA. Before the test, the samples were vacuum treated at 300℃ for more than 4h. The specific surface area, pore size and other parameters were calculated according to the BET and BJH formulas.
[0053] In this paper, the phase structure and crystallinity of zeolite materials were characterized by X-ray diffraction, and the test was carried out using a Japanese Rigaku D / max2500 X-ray diffractometer with Cu target, Kα radiation source, graphite monochromator, tube voltage 40 kV, tube current 80 mA, scanning range 5°~40°, step size 0.1°, and scanning speed 1° / min.
[0054] In this paper, the acid content of the zeolite material was measured by ammonia temperature-programmed desorption. The ammonia temperature-programmed desorption test was performed using an AutoChem II 2920 chemical adsorption instrument manufactured by Micromeritics, USA. First, under the protection of helium, the temperature was raised to 550°C at a rate of 10°C / min and maintained for 1 hour; then the temperature was lowered to room temperature (25°C) at a rate of 10°C / min, replaced with ammonia and adsorbed for 1 hour; then replaced with helium and heated to 600°C at a rate of 10°C / min.
[0055] In this paper, the crystal morphology of the zeolite material was characterized by transmission electron microscopy, using a high-resolution transmission electron microscope (TEM) from JEOL, Japan. The instrument model was JEM-2200FS field emission ultra-high resolution transmission electron microscope, with an acceleration voltage of 200KV and a point resolution of 0.19nm.
[0056] In this article, the chemical reagents used are all analytically pure chemical reagents and can be obtained by purchasing commercial products.
[0057] In this paper, in the preparation of pretreated mordenite, a support is built into the reactor.
[0058] Example 1
[0059] Put mordenite into the upper part of the support of the reactor, and put ammonia water and water into the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 15:18:100, and then close the reactor for pretreatment, the pretreatment temperature is 400°C, and the pretreatment time is 8h; then wash, filter and dry to obtain the pretreated mordenite, the drying temperature is 120°C, and the drying time is 3h. Sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water were mixed evenly and then placed in a closed reactor for reaction at 100°C for 25 hours. After the reaction was completed, the solid phase material was washed and filtered for many times, and the solid phase material was dried at 120°C for 10 hours to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water was 1.3:1.2:3.3:17:1.2:100. Then, the materials were mixed evenly according to the mass ratio of ammonium nitrate, zeolite precursor, and water of 16:15:100, treated at 85°C for 3 hours, and the treatment was circulated for 3 times; after the end, the solid phase material was further washed and filtered for many times, and then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air, and the obtained sample was numbered C1.
[0060] Example 2
[0061] Put mordenite into the upper part of the support of the reactor, and put ammonia water and water into the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 10:15:100, and then close the reactor for pretreatment, the pretreatment temperature is 450°C, and the pretreatment time is 1h; then wash, filter and dry to obtain the pretreated mordenite, the drying temperature is 120°C, and the drying time is 3h. Sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid and deionized water are mixed evenly and then loaded into a closed reactor to react at 80°C for 20 hours. After the reaction is completed, it is washed with water and filtered for multiple times, and the solid phase material is dried at 120°C for 10 hours to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid and deionized water is 1:1:2:10:1:100, and then the materials are mixed evenly according to the mass ratio of ammonium nitrate, zeolite precursor and water of 10:10:100, treated at 90°C for 2 hours, and the treatment is repeated 3 times; after the end, it is further washed with water and filtered for multiple times, and then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air, and the obtained sample is numbered C2.
[0062] Example 3
[0063] Put mordenite into the upper part of the support of the reactor, and put ammonia water and water into the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 20:25:100, and then close the reactor for pretreatment, the pretreatment temperature is 850°C, and the pretreatment time is 5h; then wash, filter and dry to obtain the pretreated mordenite, the drying temperature is 120°C, and the drying time is 3h. Sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid and deionized water were mixed evenly and then loaded into a closed reactor for reaction at 120°C for 30 hours. After the reaction was completed, the mixture was washed with water and filtered for several times, and the solid phase material was dried at 120°C for 10 hours to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid and deionized water was 2:2:4:20:2.5:100, and then the materials were mixed evenly according to the mass ratio of ammonium nitrate, zeolite precursor and water of 20:20:100, treated at 80°C for 4 hours, and the treatment was repeated 3 times; after the reaction was completed, the mixture was further washed with water and filtered for several times, and then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air, and the obtained sample was numbered C3.
[0064] Example 4
[0065] Put mordenite into the upper part of the support of the reactor, and put ammonia water and water into the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 13.5:22:100, and then close the reactor for pretreatment, the pretreatment temperature is 490°C, and the pretreatment time is 8h; then wash, filter and dry to obtain the pretreated mordenite, the drying temperature is 120°C, and the drying time is 3.5h. Sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid and deionized water were mixed evenly and then loaded into a closed reactor to react at 110°C for 22 hours. After the reaction, the mixture was washed with water and filtered for several times, and the solid phase material was dried at 120°C for 10 hours to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid and deionized water was 1.4:1.1:3.6:12:1.7:100, and then the materials were mixed evenly according to the mass ratio of ammonium nitrate, zeolite precursor and water of 16.2:15.3:100, treated at 80°C for 3 hours, and the treatment was repeated 3 times; after the reaction, the mixture was further washed with water and filtered for several times, and then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air, and the obtained sample was numbered C4.
[0066] Example 5
[0067] Put mordenite into the upper part of the support of the reactor, and put ammonia water and water into the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 11.5:23:100, and then close the reactor for pretreatment, the pretreatment temperature is 730°C, and the pretreatment time is 7h; then wash, filter and dry to obtain the pretreated mordenite, the drying temperature is 120°C, and the drying time is 2h. Sodium hydroxide, aluminum sulfate, silica gel, pretreated mordenite, ethylenediaminetetraacetic acid and deionized water were mixed evenly and then loaded into a closed reactor to react at 90°C for 25 hours. After the reaction, the solid phase material was washed and filtered for many times, and dried at 120°C for 10 hours to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum sulfate, silica gel, pretreated mordenite, ethylenediaminetetraacetic acid and deionized water was 1.5:1.3:3.4:18:1.3:100, and then the materials were mixed evenly according to the mass ratio of ammonium nitrate, zeolite precursor and water of 16.6:12:100, treated at 88°C for 3 hours, and the treatment was repeated 3 times; after the reaction, it was further washed and filtered for many times, and then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air, and the obtained sample was numbered C5.
[0068] Comparative Example 1
[0069] Sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water were mixed evenly and then placed in a closed reactor for reaction at 100°C for 25 hours. After the reaction was completed, the solid phase material was washed and filtered for many times, and the solid phase material was dried at 120°C for 10 hours to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water was 1.3:1.2:3.3:17:1.2:100. Then, the materials were mixed evenly according to the mass ratio of ammonium nitrate, zeolite precursor, and water of 16:15:100, treated at 85°C for 3 hours, and the treatment was circulated for 3 times; after the end, it was further washed and filtered for many times, and then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air, and the obtained sample was numbered C6.
[0070] Comparative Example 2
[0071] Put the mordenite in the upper part of the support of the reactor, and put ammonia water and water in the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 15:18:100, and then the closed reactor is pretreated, the pretreatment temperature is 400℃, and the pretreatment time is 8h; then the pretreated mordenite is obtained after washing, filtering and drying, the drying temperature is 120℃, and the drying time is 3h. Sodium hydroxide, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water are mixed evenly and then loaded into a closed reactor to react at 100℃ for 25h. After the reaction is completed, it is washed and filtered for many times, and the obtained solid phase material is dried at 120℃ for 10h to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water is 1.3:3.3:17:1.2:100. Then, the materials were evenly mixed according to the mass ratio of ammonium nitrate, zeolite precursor and water of 16:15:100, treated at 85°C for 3 hours, and recycled for 3 times; after completion, they were further washed and filtered for multiple times, then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air. The resulting sample was numbered C1.
[0072] Comparative Example 3
[0073] Put the mordenite in the upper part of the support of the reactor, and put ammonia water and water in the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 15:18:100, and then the closed reactor is pretreated, the pretreatment temperature is 400℃, and the pretreatment time is 8h; then the pretreated mordenite is obtained after washing, filtering and drying, the drying temperature is 120℃, and the drying time is 3h. Sodium hydroxide, aluminum nitrate, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water are mixed evenly and then put into a closed reactor to react at 100℃ for 25h. After the reaction is completed, it is washed and filtered for many times, and the obtained solid phase material is dried at 120℃ for 10h to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum nitrate, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water is 1.3:1.2:17:1.2:100. Then, the materials were evenly mixed according to the mass ratio of ammonium nitrate, zeolite precursor and water of 16:15:100, treated at 85°C for 3 hours, and recycled for 3 times; after completion, they were further washed and filtered several times, then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air. The resulting sample was numbered C8.
[0074] Comparative Example 4
[0075] Put the mordenite in the upper part of the support of the reactor, and put ammonia water and water in the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 15:18:100, and then the closed reactor is pretreated, the pretreatment temperature is 400℃, and the pretreatment time is 8h; then the pretreated mordenite is obtained after washing, filtering and drying, the drying temperature is 120℃, and the drying time is 3h. Sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite and deionized water are mixed evenly and then loaded into a closed reactor to react at 100℃ for 25h. After the reaction is completed, it is washed and filtered for many times, and the obtained solid phase material is dried at 120℃ for 10h to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite and deionized water is 1.3:1.2:3.3:17:100. Then, the materials were evenly mixed according to the mass ratio of ammonium nitrate, zeolite precursor and water of 16:15:100, treated at 85°C for 3 hours, and recycled for 3 times; after completion, they were further washed and filtered several times, then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air. The resulting sample was numbered C9.
[0076] Comparative Example 5
[0077] Put the mordenite in the upper part of the support of the reactor, and put ammonia water and water in the lower part of the support of the reactor, wherein the weight ratio of mordenite, ammonia water and water is the mass ratio of zeolite, ammonia water and water = 15:1:100, then the closed reactor is pretreated, the pretreatment temperature is 120℃, and the pretreatment time is 8h; then the pretreated mordenite is obtained after washing, filtering and drying, the drying temperature is 120℃, and the drying time is 3h. Sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water are mixed evenly and then put into a closed reactor to react at 100℃ for 25h. After the reaction is completed, it is washed and filtered for many times, and the obtained solid phase material is dried at 120℃ for 10h to obtain a zeolite precursor; wherein the mass ratio of sodium hydroxide, aluminum nitrate, white carbon black, pretreated mordenite, ethylenediaminetetraacetic acid, and deionized water is 0.3:0.5:0.5:10:0.1:100. Then, the materials were evenly mixed according to the mass ratio of ammonium nitrate, zeolite precursor and water of 16:15:100, treated at 85°C for 3 hours, and recycled for 3 times; after completion, they were further washed and filtered for multiple times, then dried at 120°C for 10 hours, and finally calcined at 500°C for 10 hours in the presence of air. The resulting sample was numbered C10.
[0078] Table 1 Physical and chemical properties of samples obtained in various embodiments and comparative examples
[0079]
[0080]
[0081] Note: The present invention uses the sample obtained in Example 1 as a reference, and its crystallinity is set to 100%. The relative crystallinity of all other samples is obtained by comparing with the crystallinity of the reference. The original acid content of mordenite is 0.167 mmol / g.
Claims
1. A mordenite zeolite having a mordenite structure, characterized by a transmission electron microscope as a single crystal particle with a hollow structure, wherein the center of the crystal is in a hollow state.
2. The mordenite according to claim 1, characterized in that: The particle diameter of the mordenite crystal is 90 to 1000 nm, preferably 100 to 900 nm; the shell thickness of the mordenite crystal particle is 25 to 360 nm, preferably 30 to 300 nm.
3. The mordenite according to claim 1, characterized in that: The specific surface area of mordenite is 270~590m 2 / g, preferably 300 to 560 m 2 / g; the pore volume of mordenite is 0.1~0.3cm 3 / g.
4. The mordenite according to claim 1, characterized in that: The acid content of mordenite is 0.05 to 0.24 mmol / g.
5. The mordenite according to claim 1, characterized in that: The silicon-aluminum ratio of mordenite is 9 to 50, preferably 10 to 45, as calculated as oxide.
6. A method for preparing mordenite, the preparation method comprising the following steps: (1) under pretreatment conditions, the mordenite is contacted with an ammonia-containing gas for pretreatment, and after the treatment is completed, the mordenite is washed, separated and dried to obtain the pretreated mordenite; (2) under reaction conditions, the pretreated mordenite, the aluminum-containing compound, the alkali source, the silicon-containing compound, ethylenediaminetetraacetic acid, and water are uniformly mixed and reacted, and the product obtained by the reaction is washed with water, separated, and dried to obtain a zeolite precursor; (3) The hollow mordenite is obtained by treating the zeolite precursor under calcination conditions.
7. A method for preparing mordenite, the preparation method comprising the following steps: Step (I): synthesizing a zeolite precursor, the synthesis steps comprising: (1) under pretreatment conditions, the mordenite is contacted with an ammonia-containing gas for pretreatment, and after the treatment is completed, the mordenite is washed, separated and dried to obtain the pretreated mordenite; (2) under reaction conditions, the pretreated mordenite, the aluminum-containing compound, the alkali source, the silicon-containing compound, ethylenediaminetetraacetic acid, and water are uniformly mixed and reacted, and the product obtained by the reaction is washed with water, separated, and dried to obtain a zeolite precursor; Step (ii): Under ammonium exchange conditions, the obtained zeolite precursor is subjected to ammonium exchange treatment, and then washed, separated, dried and calcined to obtain hydrogen-type hollow mordenite.
8. The method for preparing mordenite according to claim 6 or 7, characterized in that: The pretreatment in step (1) is a gas-solid two-phase reaction between mordenite and ammonia-containing gas, and the mordenite is contacted with the ammonia-containing gas for pretreatment; the reaction process is that a support is provided in the reactor, the mordenite is placed on the support, and ammonia water and water are added to the lower part of the reactor support; the mass ratio of ammonia water, mordenite and water is 12-28: 8-25:100, preferably 15-25: 10-20:100;.
9. The method for preparing mordenite according to claim 6 or 7, characterized in that: The pretreatment conditions in step (1) are as follows: the pretreatment temperature is 400 to 900° C., preferably 450 to 850° C., and the pretreatment time is 0.5 to 6 hours, preferably 1 to 5 hours.
10. The method for preparing mordenite according to claim 6 or 7, characterized in that: The alkali source in step (2) is an inorganic base, and the inorganic base is one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide.
11. The method for preparing mordenite according to claim 6 or 7, characterized in that: The aluminum-containing compound in step (2) is an aluminum-containing inorganic salt, and the acid ion of the aluminum-containing inorganic salt is one or more of sulfate, aluminate, nitrate and chloride.
12. The method for preparing mordenite according to claim 6 or 7, characterized in that: The aluminum-containing compound in step (2) is selected from one or more of sodium aluminate, aluminum sulfate, aluminum chloride and aluminum nitrate.
13. The method for preparing mordenite according to claim 6 or 7, characterized in that: The silicon-containing compound in step (2) is one or more of white carbon black, silica gel, and silica sol.
14. The method for preparing mordenite according to claim 6 or 7, characterized in that: In step (2), the mass ratio of the alkali source, the aluminum-containing compound, the silicon-containing compound, the pretreated mordenite, the ethylenediaminetetraacetic acid, and water is 0.8-2.5:0.8-2.1:2.5-6:8-25:0.8-3:100, preferably 1-2:1-2:2-4:10-20:1-2.5:
100.
15. The method for preparing mordenite according to claim 6 or 7, characterized in that: The reaction conditions in step (2) are: reaction temperature 70-150° C., preferably 80-120° C., and reaction time 19-32 h, preferably 20-30 h.
16. The method for preparing mordenite according to claim 6 or 7, characterized in that: The drying conditions in step (2) are: drying temperature is 80 to 150° C., and drying time is 1 to 20 hours.
17. The method for preparing mordenite according to claim 6 or 7, characterized in that: The ammonium exchange treatment in step (ii) is to mix the zeolite precursor obtained after drying in step (2), the ammonium salt and water for ion exchange treatment. The mass ratio of the zeolite precursor, the ammonium salt and the water obtained after drying in step (2) is 8 to 25:8 to 25:100, preferably 10 to 20:10 to 20:
100. The ammonium salt can be one or more of ammonium nitrate, ammonium chloride and ammonium sulfate, preferably ammonium nitrate.
18. The method for preparing mordenite according to claim 6 or 7, characterized in that: The ammonium exchange conditions in step (ii) are: the ion exchange temperature is 70-100° C., preferably 80-90° C., and the ion exchange time is 1-5 h, preferably 2-4 h.
19. The method for preparing mordenite according to claim 6 or 7, characterized in that: The drying conditions in step (ii) are as follows: drying temperature is 80-150° C., and drying time is 1-20 hours.
20. The method for preparing mordenite according to claim 6 or 7, characterized in that: The calcination in step (ii) is carried out in the presence of an oxygen-containing gas, wherein the volume fraction of oxygen in the oxygen-containing gas is 10 to 100%. The calcination conditions are as follows: the calcination temperature is 400 to 600° C., and the high-temperature calcination treatment is performed for 1 to 10 hours.
Citation Information
Patent Citations
Method for synthesizing mesoporous mordenite
CN102190316A
Pillared layered mordenite, and preparation method thereof
CN106517239A
Hollow hierarchical pore composite molecular sieve as well as preparation method and application thereof
CN115974095A
Mordenite zeolite and production method therefor
US20190367378A1
Hollow zeolite type catalysts with varying framework and zeolite topologies
WO2017141132A1